Complementary Chromophore Decoration in NU‐1000 via Solvent‐Assisted Ligands Incorporation: Efficient Energy Transfer within the Metal‐Organic Frameworks. (28th January 2019) - Oh, Jung Suk; Park, Kyoung Chul; Gupta, Gajendra; Lee, Chang Yeon
Abstract : BODIPY‐incorporated solvent‐assisted ligand incorporation metal‐organic frameworks (SALI‐MOFs) were designed and synthesized using NU‐1000 and carboxylic acid functionalized BODIPY moieties by the solvent‐assisted ligand incorporation (SALI) approach. SALI‐MOFs were characterized by various technique including powder X‐ray diffraction, scanning electron microscope, N2 adsorption/desorption isotherms, Fourier transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy. The SALI‐MOFs were found to have cooperative light‐harvesting properties and shown to possess efficient singlet oxygen ( 1 O2 ) generation ability. Abstract : BODIPY‐incorporated solvent‐assisted ligand incorporation (SALI) metal‐organic frameworks were designed and synthesized using NU‐1000 and functionalized BODIPY moieties by the SALI approach. The SALI‐I2BDP was found to have cooperative light‐harvesting properties and shown efficient singlet oxygen ( 1 O2 ) generation ability.